Foot Conditions among Homeless Persons: A Systematic Review. - Matthew J To; Thomas D Brothers; Colin Van Zoost (PLoS ONE, 2016)
Introduction Foot problems are common among homeless persons, but are often overlooked. The objectives of this systematic review are to summarize what is known about foot conditions and associated interventions among homeless persons. Methods A literature search was conducted on MEDLINE (1966-2016), EMBASE (1947-2016), and CINAHL (1982-2016) and complemented by manual searches of reference lists. Articles that described foot conditions in homeless persons or associated interventions were included. Data were independently extracted on: general study characteristics; participants; foot assessment methods; foot conditions and associated interventions; study findings; quality score assessed using the Downs and Black checklist. Results Of 333 articles screened, 17 articles met criteria and were included in the study. Prevalence of any foot problem ranged from 9% to 65% across study populations. Common foot-related concerns were corns and calluses, nail pathologies, and infections. Foot pathologies related to chronic diseases such as diabetes were identified. Compared to housed individuals across studies, homeless individuals were more likely to have foot problems including tinea pedis, foot pain, functional limitations with walking, and improperly-fitting shoes. Discussion Foot conditions were highly prevalent among homeless individuals with up to two thirds reporting a foot health concern, approximately one quarter of individuals visiting a health professional, and one fifth of individuals requiring further follow-up due to the severity of their condition. Homeless individuals often had inadequate foot hygiene practices and improperly-fitting shoes. These findings have service provision and public health implications, highlighting the need for evidence-based interventions to improve foot health in this population. An effective interventional approach could include optimization of foot hygiene and footwear, provision of comprehensive medical treatment, and addressing social factors that lead to increased risk of foot problems. Targeted efforts to screen for and treat foot problems could result in improved health and social outcomes for homeless individuals.